(untitled) (Journal of Asian Development Studies, 2026)
Despite the sophisticated frameworks in modern economics that relate inputs to outputs and define the drivers of economic growth, a critical philosophical gap remains. The study of the Holy Quran from an economic perspective, focusing on verses that discuss productive resources or economic flourishing, reveals a distinct paradigm. The current study is the first attempt to perform a thematic content analysis of the Holy Quran and to develop a comprehensive data inventory, identifying all the verses that discuss productive resources, production andeconomic prosperity or decline of an individual. This aim was achieved by designing and conducting a rigorous thematic content analysis of all 114 Surahs and 30 Juz of the Holy Quran, resulting in the identification of 108 verses across 30 Surahs as production-relevant data. The content analysis resulted in sub-categorising these verses into two main themes: The productive resources and Output preliminaries. The study catalogues all the primary natural resources that are discussed in the Holy Quran relevant to the productive process, specifically rain, marine resources, and utilities generated from livestock, alongside the necessity of human effort to exploit these resources. In addition, certain preliminaries must be met; if not, both the final output andhuman effort can be destroyed. These include arrogance, disbelief, denial of Supreme Authority, and failure to consider the due share of the poor in the output. Eventually, the study develops a useful repository of verses relevant to the theme of production in economics.